Anthropometric predictors of hamstring graft size in anterior cruciate ligament reconstruction - T. P., Rinshad; Joseph, Babu; Mammu, Sharafuddeen; P., Uwais; Hussain K., Nejil; Pawaskar, Siddarth (International Journal of Research in Orthopaedics, 2024)
Background: The anterior cruciate ligament (ACL) is commonly injured in the knee joint, necessitating surgical reconstruction where quadrupled hamstring tendon autografts are frequently utilized for their favourable outcomes. Predicting the appropriate dimensions of these grafts is essential for surgical success. This study aims to investigate whether simple anthropometric measurements-height, weight, body mass index (BMI), thigh length, and circumference-can predict the length and diameter of quadrupled hamstring tendons used in ACL reconstruction. Methods: This cross-sectional study included 45 patients undergoing ACL reconstruction with quadrupled hamstring autografts at department of orthopaedics, Renai Medicity Kerala, India. Preoperative anthropometric measurements were correlated with intraop graft dimensions using Pearson correlation and SPSS statistical software (version 22). Results: Taller patients exhibited a positive correlation with graft diameter (p=0.028). Height and thigh length correlated positively with both gracilis and semitendinosus tendon lengths (p<0.001). Thigh circumference correlated positively with semitendinosus length (p=0.005), while weight, BMI, and other measures did not significantly correlate with graft dimensions. Conclusions: Anthropometric measurements, particularly height and thigh length, serve as valuable predictors for hamstring graft dimensions in ACL reconstruction. These findings may assist surgeons in selecting appropriate grafts and optimizing surgical outcomes.